Implementation of Work Culture in Improving Human Resource Performance and Service Quality - Sofyan A. Ointu; Lindanur Sipatu; Rosida adam; Arie kurniawan (Al-Qalam Institue, 2025)
This study aims to explore the impact of Human Resources (HR) play a crucial role in the success of any organization, including hospitals. A strong work culture, encompassing the values ​​of professionalism, cooperation, excellent service, innovation, and exemplary behavior, can improve the quality of hospital services. However, the implementation of work culture at Regional General Hospital still faces technical and facility constraints that hinder its effectiveness. This study aims to evaluate the impact of work culture implementation on HR performance and service quality. The method used was a qualitative case study with an explanatory approach, using purposive sampling to select eight informants consisting of five nurses and three patients. Data were analyzed using the Nvivo 12 Plus application for Windows. The results showed that although work culture values ​​had been implemented, obstacles such as information system disruptions, changes in BPJS policies, and limited facilities still hampered optimal implementation. This study suggests the need for infrastructure improvements and managerial support to enhance the implementation of work culture and service quality. In conclusion, the synergy between a strong work culture and adequate system support will improve service quality in hospitals.